Sequence specific recognition of ssDNA by fluorophore 3-hydroxyflavone - EROĞLU, MEHMET SAYIP; SENNAROĞLU BOSTAN, MÜGE (ELSEVIER SCIENCE SA, 2015)
A fully water soluble 3-hydroxyflavone (3HF) derivative, N-(3-hydroxy-4'-flavonyl)-N,N,N-trimethylammonium sulfate (3HFNMe3) was synthesized. Investigation of its emissions at varying wavelengths revealed that it had three emission bands of normal (N*), anionic (A*) and tautomeric (T*), in ultrapure water. Recognition of single-stranded ten ssDNA chains, having different nucleotide sequences was studied, using the ratiometric change of the intensities of the two bands (A*/T*), depending upon the varying environment of the 3HFNMe3 with different ssDNA chains. Addition of the ssDNA chains to the 3HFNMe3 solution caused gradual quenching of the A* band and had almost no effect on the T*. band. As the ratios of the two bands (A*/T*) vs increasing amount of the ssDNAs generated characteristic curves for each ssDNA chain, it became possible to identify the chains with their characteristic curves. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Fluorophore; 3-Hydroxyflavone; DNA; Specific recognition; Spectroscopic methods; PROTON-TRANSFER; FLUORESCENCE; PROBES; ENVIRONMENT